PENGEMBANGAN MUTU SEKOLAH - Dwi Deswary (Perspektif Ilmu Pendidikan, 2006)
Study on the school quality improvement prescribes that the school quality can be improved through quality socialization in a number of phases. Each school can do a number of activities such as creates good working conditions; formulates vision, mission, and institutional objectives of the school; does SWOT analysis; chooses problem solving alternatives; develops plans and programs to improve the quality; conducts evaluation on the program implementation; and sets objectives of quality improvement. To avoid inefficiency, a set of quality improvement tools needs to apply.